A rare case of floating clavicle and a novel technique for stabilizing the sternoclavicular joint. Issue 1 (January 2015) - Thyagarajan, David; Webb, Mark; Wallace, Angus
We present the first ever case report of a floating clavicle with a unique combination of a posterior sternoclavicular joint dislocation and an associated grade III acromioclavicular joint dislocation. We treated this injury surgically by stabilizing both ends of clavicle using a polyester surgical mesh device (LockDown™; Mandaco 569 Limited, Redditch, UK; previously called the Nottingham Surgilig).